2019
DOI: 10.1111/cei.13252
|View full text |Cite
|
Sign up to set email alerts
|

Perceived health of patients with common variable immunodeficiency – a cluster analysis

Abstract: Common variable immunodeficiency (CVID) is a complex disease with various influences on perceived health, which correlate with different outcomes, including new morbidity and mortality. Our hypothesis was that CVID patients fall into distinct clusters of perceived health which can inform care. Ward hierarchical cluster analysis and K-means cluster analysis were performed on data of 209 CVID patients to identify subgroups regarding their self-reported physical and mental health status, assessed by the physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In a sample of patients with common variable immunodeficiency, Bayrhuber et al found a four-group classification after clustering participants’ combined perceived mental and physical health scores on the SF-12. 36 Although a similar design to that used by Bayrhuber et al for clustering perceived health variables was followed in this study, the two-step cluster analysis used in the current study is considered to be a more advantageous procedure compared with hierarchical approaches. 48 In these previous studies, clusters representing better self-reported health status were positively associated with a better psychosocial outcome 37 and other relevant variables such as work ability and health literacy, 36 while the negative psychological profile identified in patients with CVD was associated with mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a sample of patients with common variable immunodeficiency, Bayrhuber et al found a four-group classification after clustering participants’ combined perceived mental and physical health scores on the SF-12. 36 Although a similar design to that used by Bayrhuber et al for clustering perceived health variables was followed in this study, the two-step cluster analysis used in the current study is considered to be a more advantageous procedure compared with hierarchical approaches. 48 In these previous studies, clusters representing better self-reported health status were positively associated with a better psychosocial outcome 37 and other relevant variables such as work ability and health literacy, 36 while the negative psychological profile identified in patients with CVD was associated with mortality.…”
Section: Discussionmentioning
confidence: 99%
“… 36 Although a similar design to that used by Bayrhuber et al for clustering perceived health variables was followed in this study, the two-step cluster analysis used in the current study is considered to be a more advantageous procedure compared with hierarchical approaches. 48 In these previous studies, clusters representing better self-reported health status were positively associated with a better psychosocial outcome 37 and other relevant variables such as work ability and health literacy, 36 while the negative psychological profile identified in patients with CVD was associated with mortality. 26 In the present study, the cluster representing higher self-reported mental and physical health was also associated with better SES and psychological outcomes, reinforcing the relevance of considering clusters derived from self-reported health status in patients with a chronic condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is frequently associated with the development of bronchiectasis over time (5). Additionally, around 50% of CVID patients have secondary noninfectious lymphoproliferative, autoimmune and inflammatory complications like autoimmune cytopenias, granulomatous disease, splenomegaly and lymphadenopathy, interstitial lung disease, enteropathy and hepatopathy (6) often contributing to a significantly reduced quality of life and increased morbidity and mortality (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%